Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2017)
Light harvesting donor-acceptor assemblies are indispensable to efficiently tap photons. In an attempt to improve the light harvesting efficiency of an acceptor doped assembly, we design and synthesize a donor-acceptor-donor triad which exhibits an exceptional intramolecular energy transfer with excellent efficiency. Moreover, a facile cascade energy transfer (energy funnelling) is observed in the presence of a series of second acceptors (63-91% efficiency) with tunable emission colours. Self-assembled nanosheets formed by the triad in the presence of acceptors exhibit cascade energy transfer assisted tunable emission. In addition, use of chiral acceptors induces chirality to the triad and results in the formation of chiral nanosheets alongwith cascade energy transfer. Here chiral induction, nanosheet formation and cascade energy transfer in the presence of chiral acceptors are used as tools to probe the intercalation of acceptor molecules in the donor scaffold.

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Boron-conjugated pyrenes as fluorescence-based molecular probes and security markers - Wakchaure, Vivek Chandrakant; Das, Tamal; Babu, Sukumaran Santhosh (ChemPlusChem, 2019)
Boron-embedded aromatic hydrocarbons are a class of molecules known for their distinct electronic and/or optoelectronic properties and are thus suitable for many potential applications. Among those, boronic ester and acid containing molecules have been widely used for sensing and molecular recognition applications, respectively. We compared the sensing and molecular recognition properties of two boron-containing pyrene derivatives for fluoride and glucose sensing applications. The presence of four boronate ester groups enabled fluoride ion sensing at the mu M level. The boronic acid derivative is very selective towards glucose compared to other saccharides. Furthermore, we used the mechano-responsive fluorescence changes and self-assembly of these derivatives, respectively, for fluorescence-based inkless and ink (water)-based writing in invisible security labeling applications.
Keywords: boron; carbohydrates; mechanoluminescence; pyrene; sensors

Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.

Charge transfer liquid: a stable donor-acceptor interaction in the solvent-free liquid state - Wakchaure, Vivek Chandrakant; Pillai, Lekshmi, V; Goudappagouda; Ranjeesh, Kayaramkodath Chandran; Chakrabarty, Suman; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Charge-transfer complexes have been an inspiration to develop many functional soft materials. However, most of those studies have focused on solution based assemblies wherein the explicit control of solvents and their polarity are crucial. In this context, we explore an efficient and stable charge transfer liquid using a solvent-free liquid dialkoxynaphthalene donor and a naphthalenediimide acceptor. It has been observed that irrespective of the donor-acceptor ratio, the charge-transfer liquid exhibited an unprecedented stability and retained characteristic features even at increased temperatures. The underlying intermolecular interactions leading to efficient CT have been examined by NMR techniques together with theoretical modelling studies. The concept of charge transfer liquid will be highly beneficial for the development of processable optoelectronically active materials.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Imidazole-linked crystalline two-dimensional polymer with ultrahigh proton-conductivity - Ranjeesh, Kayaramkodath Chandran; Ilathvalappil, Rajith; Veer, Sairam Dnyaneshwar; Peter, Joseph; Wakchaure, Vivek Chandrakant; Goudappagouda; Raj, K. Vipin; Kurungot, Sreekumar; Babu, Sukumaran Santhosh (Journal of the American Chemical Society, 2019)
Proton-exchange membrane fuel cells are promising energy devices for a sustainable future due to green features, high power density, and mild operating conditions. A facile proton-conducting membrane plays a pivotal role to boost the efficiency of fuel cells, and hence focused research in this area is highly desirable. Major issues associated with the successful example of Nafion resulted in the search for alternate proton conducting materials. Even though proton carrier loaded crystalline porous organic frameworks have been used for protonconduction, the weak host-guest interactions limited their practical use. Herein, we developed a crystalline 2D-polymer composed of benzimidazole units as the integral part, prepared by the condensation of aryl acid and diamine in polyphosphoric acid medium. The imidazole linked-2D-polymer exhibits ultrahigh proton conductivity (3.2 X 10(-2) S cm(-1)) (at 95% relative humidity and 95 degrees C) in the pristine state, which is highest among the undoped porous organic frameworks so far reported. The present strategy of a crystalline proton-conducting 2D-polymer will lead to the development of new high performing crystalline solid proton conductor.

Dual mode selective detection and differentiation of TNT from other nitroaromatic compounds - Patil, Goudappagouda; Dongre, Sangram D.; Das, Tamal; Babu, Sukumaran Santhosh (Journal of Materials Chemistry A, 2020)
Selective detection of explosives, especially TNT, is a highly desirable area of research and various explosives detection devices including fluorescent sensors are already in place. However, multi-mode sensors will be more useful and reliable than conventional fluorescent ``Turn Off'' sensors. One of the challenges is the development of selective sensors to prevent illegal transport of commonly used explosive TNT through on-the-spot analysis. In this context, we report a fluorescent polymer-based selective detection of TNT using both fluorometric and colorimetric signals. In addition, colorimetric differentiation of TNT from other nitroaromatic compounds is made possible by complexing with various amines. Even though many other sensors are available for TNT, the current demonstration is unique in terms of selectivity, sensitivity, reliability, portability, and rapidity of results. The as-developed explosive detection kit can be useful in both civilian and military operations to trace the illegal transport of TNT as well as for post-explosion analysis.

Self-assembled helical arrays for the stabilization of the triplet state - Nidhankar, Aakash D.; Goudappagouda; Kumari, Divya S. Mohana; Chaubey, Shailendra Kumar; Nayak, Rashmi; Gonnade, Rajesh G.; Kumar, G. V. Pavan; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2020)
Room-temperature phosphorescence of metal and heavy atom-free organic molecules has emerged as an area of great potential in recent years. A rational design played a critical role in controlling the molecular ordering to impart efficient intersystem crossing and stabilize the triplet state to achieve room-temperature ultralong phosphorescence. However, in most cases, the strategies to strengthen phosphorescence efficiency have resulted in a reduced lifetime, and the available nearly degenerate singlet-triplet energy levels impart a natural competition between delayed fluorescence and phosphorescence, with the former one having the advantage. Herein, an organic helical assembly supports the exhibition of an ultralong phosphorescence lifetime. In contrary to other molecules, 3,6-phenylmethanone functionalized 9-hexylcarbazole exhibits a remarkable improvement in phosphorescence lifetime (>4.1 s) and quantum yield (11 %) owing to an efficient molecular packing in the crystal state. A right-handed helical molecular array act as a trap and exhibits triplet exciton migration to support the exceptionally longer phosphorescence lifetime.
Keywords: carbazole; helicity; phenylmethanone; ultralong phosphorescence; waveguiding

Tuning phosphorescence features of triphenylamines by varying functional groups and intermolecular interactions - Goudappagouda; Asokan, Kiran; Nayak, Rashmi; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Dyes and Pigments, 2020)
Organic room temperature phosphorescent materials are known for their synthetic feasibility, tunable phosphorescence wavelength and lifetime, etc. Hence new design strategies have been applied on various fluorophores to improve phosphorescence features. Among those, triphenylamines are phosphorescence active due to the presence of nitrogen atom, propeller molecular structure, and intermolecular interactions in the crystal state. Here we have studied the room temperature phosphorescence of a series of triphenylamines with various functional groups. Detailed studies have shown that the phosphorescence can be fine-tuned by functional group modification. A long phosphorescence lifetime around 100 ms at room temperature in air can be achieved by the interplay of intermolecular interactions, singlet-triplet energy gap and extent of intersystem crossing using functional group variation. Interestingly, an exciplex assisted ultralong phosphorescence lifetime (more than 20 times) is observed for a combination of triphenylamine and naphthalenemonoimide in air.
Keywords: Exciplex; fluorescence; Phosphorescence; triphenylamine

Aggregation-induced phosphorescence of an anthraquinone based emitter - Goudappagouda; Nidhankar, Aakash D.; Nayak, Rashmi A.; Babu, Sukumaran Santhosh (Organic & Biomolecular Chemistry, 2021)
Room temperature phosphorescence (RTP) of metal-free organic molecules is a hot topic of current research interest. RTP can be enhanced through aggregation, crystallization, and the support of polymers and host-guest assemblies. The characteristics of highly phosphorescent aggregates formed from conventional chromophores make them ideal candidates for many potential applications. In this direction, we focused on the aggregation-induced phosphorescence of an anthraquinone derivative AqC6 in solution and in crystal state. The weakly emissive dilute solution exhibits a tunable emission with enhanced intensity and room temperature phosphorescence by increasing the concentration and solvent-antisolvent combination. The enhanced phosphorescence of crystals has been recreated in the solution by making use of aggregation. Interestingly, the support of PMMA enabled AqC6 to achieve enhanced processability, phosphorescence lifetime (174 ms) and quantum yield (5%).

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

Efficient metal-free organic room temperature phosphors - Nidhankar, Aakash D.; Goudappagouda; Wakchaure, Vivek C.; Babu, Sukumaran Santhosh (Chemical Science, 2021)
An innovative transformation of organic luminescent materials in recent years has realised the exciting research area of ultralong room-temperature phosphorescence. Here the credit for the advancements goes to the rational design of new organic phosphors. The continuous effort in the area has yielded wide varieties of metal-free organic systems capable of extending the lifetime to several seconds under ambient conditions with high quantum yield and attractive afterglow properties. The various strategies adopted in the past decade to manipulate the fate of triplet excitons suggest a bright future for this class of materials. To analyze the underlying processes in detail, we have chosen high performing organic triplet emitters that utilized the best possible ways to achieve a lifetime above one second along with impressive quantum yield and afterglow properties. Such a case study describing different classes of metal-free organic phosphors and strategies adopted for the efficient management of triplet excitons will stimulate the development of better candidates for futuristic applications. This Perspective discusses the phosphorescence features of single- and multi-component crystalline assemblies, host-guest assemblies, polymers, and polymer-based systems under various classes of molecules. The various applications of the organic phosphors, along with future perspectives, are also highlighted.

Excimer to exciplex transition through realization of donor-acceptor interactions in luminescent solvent-free liquids - Wakchaure, Vivek Chandrakant; Goudappagouda; Das, Tamal; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Nanoscale, 2021)
Luminescent solvent-free organic liquids are known for their enhanced quantum yield, color tunability, and availability of a matrix for other dopants to generate hybrid luminescent materials with improved features for newer applications. Herein, we report a donor-acceptor based luminescent ``exciplex liquid'' by utilizing the slightly different electron affinity of the acceptor molecules. A red-shifted broad exciplex emission exhibited by the donor-acceptor pair even at a lower concentration of the acceptor (0.001 equiv.) indicates high efficiency in the solvent-free state. A detailed NMR study revealed weak intermolecular interactions between the donor and acceptor in the solvent-free matrix that stabilizes the exciplex liquid. The failure of structurally similar solid counterparts to form an exciplex confirms the advantage of the available supportive liquid matrix. Besides, the luminescent exciplex liquid is found efficient in sensing application, which is unachievable by either the individual liquids or their solid counterparts. Here, a transition of a donor-acceptor pair from a solid to solvent-free liquid results in a new hybrid liquid that can be an alternative for solid sensor materials.

Donor-acceptor based solvent-free organic liquid hybrids with exciplex emission and room temperature phosphorescence - Wakchaure, Vivek Chandrakant; Veer, Sairam D.; Nidhankar, Aakash D.; Goudappagouda; Nayak, Rashmi; Asokan, Kiran; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Chemical Communications, 2022)
Solvent-free organic liquids are well-known for their excellent luminescence features. Hence, the recent developments in this area have marked them as potential emitters with high quantum yield and enhanced processability. The support of an available liquid matrix enables doping to deliver hybrid liquids with intriguing luminescence features. In this direction, we report solvent-free liquid donor-acceptor pairs with exciplex emission and room temperature phosphorescence at very low acceptor loading. The underlying weak intermolecular interactions have been revealed by 2D NMR techniques and theoretical calculations. The formation of large-area thin films by exciplex and phosphorescent liquid hybrids will encourage the development of scalable lighting and display materials.

Highly efficient and reusable polymer supported palladium catalyst for copper free sonogashira reaction in water - Sruthi, Pambingal Rajan; Nimmi, Puthan Purayil; Babu, Sukumaran Santhosh; Anas, Saithalavi (ChemistrySelect, 2022)
Development of a novel, greener and efficient heterogeneous catalytic system for copper free Sonogashira reaction in water is described. This novel catalyst can be easily prepared by a simple method through synthetic modification of nitrile group in Polyacrylonitrile (PAN) using monoethanolamine (MEA) followed by its complexation with palladium chloride (PdCl2). The resulting polymer Pd complex (mPAN-Pd) was characterized by means of Fourier Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), Inductively Coupled Mass Spectrometry (ICP-MS) and X-ray Photo Electron Spectroscopy (XPS) analyses. mPAN-Pd was then explored as highly efficient heterogeneous catalyst for Sonogashira coupling reaction under copper and ligand free conditions in water affording the corresponding coupling products up to 97 % isolated yield. Moreover, the catalyst was recovered by simple filtration after the reaction and reused for next 5 cycles with excellent stability and activity. This is the first report on the use of ethanolamine modified PAN Pd (II) complex as an efficient heterogeneous catalyst for a coupling reaction.
Keywords: catalysis; green chemistry; Palladium; Polymer Support; Sonogashira coupling

Donor strapped perylene bisimide macrocycle and its lemniscate dimer with extended charge separation - Veer, Sairam Dnyaneshwar; Goswami, Tanmay; Ravindranathan, Sapna; Gonnade, Rajesh; Kharbanda, Nitika; Ghosh, Hirendra N.; Babu, Sukumaran Santhosh (Inorganic Chemistry Frontiers, 2023)
Macrocyclic structures are fascinating due to their unique design and capability to place chromophores in specific orientations, resulting in exciting optoelectronic properties. However, the synthetic challenges limit the broad exploration of such systems. Herein, we report a thiophene-diacetylene-based ring strapped perylene bisimide macrocycle and its notably different electron transfer features. Single-crystal analysis of the macrocycle pointed to the nearly orthogonal placement of donor-acceptor units, facilitating better electronic communication between them. Interestingly, introduction of an alkyl substituent on the peripheral thiophene ring opened the possibility of forming a higher oligomer macrocycle consisting of two strapped perylene bisimide units. Diffusion and two-dimensional NMR experiments provided insight into the structure of the figure-eight-shaped lemniscate dimer. Transient absorption measurements showed faster electron transfer and extended stabilization of the charge-separated state. The thiophene-diacetylene-based ring is a better donor unit to facilitate rapid electron transfer and extended charge separation in the macrocycle and its lemniscate dimer. The new macrocycle design enables the formation of higher analogs equally capable of stabilizing the charge-separated state. Donor-acceptor (D-A) macrocycle designs position the respective units to achieve ultrafast electron transfer precisely and an extended charge-separated state. Here, we report a D-A macrocycle and its lemniscate dimer molecule with exciting electron transfer features.

Donor-acceptor-based two-dimensional polymer as a supercapacitor electrode with long cycling stability - Bhagyasree, T. M.; Puthiyaveetil, Priyanka Pandinhare; Kumar, Viksit; Asokan, Kiran; Sreekumar, K.; Babu, Sukumaran Santhosh (New Journal of Chemistry, 2023)
The high demand for energy and energy-storage devices urged organic 2D polymers as a potential candidate in this area. One of the major attractions of 2D polymers in electrochemical applications is their long cycling stability due to their rigid and porous structure. Herein, we developed a 2D polymer comprised of donor-acceptor units exhibiting reasonably good performance as a supercapacitor. The 2D polymer displayed a maximum specific capacitance of 218 F g-1 at a current rate of 0.1 A g-1, a higher power density of 4648.35 W kg-1, and an energy density of 7.05 W h kg-1. In a cycling stability test, it demonstrated a capacitance retention of 70% over 10 000 continuous charge-discharge cycles at a current rate of 2.5 A g-1. Such long cycling stability was attributed to the donor-acceptor units and the crystalline nature of the polymer. The sensible selection of the building blocks of the 2D polymers is crucial for the performance and hence provides scope for improvement. An organic donor-acceptor-based 2D polymer, a promising candidate for energy storage devices, displays a specific capacitance of 218 F g-1, a power density of 4648.35 W kg-1, an energy density of 7.05 W h kg-1, and a capacitance retention of 70% over 10 000 cycles.

Functionalized CNT-azobenzene-PVA-based self-healing aqueous gel as a conductive photo-responsive actuator - Narayanan, Aswini; Bhagyasree, T. M.; Torris, Arun; Babu, Sukumaran Santhosh (Journal of materials chemistry C, 2023)
Conductive gels have gained attention from researchers owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, etc. Photo-responsive conductance switching gels can make their way into various applications, including contact-free remote-controlled manipulation of the materials, implantable synthetic organs, and optical switches. Herein, we report an aqueous gel with boronic acid containing azobenzene crosslinker as the light-responsive part that can undergo reversible cis-trans isomerization on irradiation with UV-vis light and catechol functionalized single-walled carbon nanotube as a conductive part producing a self-healing aqueous gel with PVA. The 3D crosslinked gel network formed through the formation of boronic ester and hydrogen bonding between hydroxyl and boronic acid groups was confirmed using scanning electron microscopy, X-ray microtomography, and rheological experiments. Rheology results show that gel is a viscoelastic material with immediate self-healing properties. The presence of functionalized SWCNT in the gel matrix enhances the stability and results in a conductivity of up to 3.5 S cm-1 with a loading of 5 wt%. The gel network exhibits a photoresponsive conductance switching from 10 to 60 mu A with UV and visible light irradiation, respectively. The molecular level motions during the isomerization of azobenzene lead to macroscopic dynamic changes that can find applications in soft actuators. The photoresponsive conductivity switching and dynamic movements of the films make the present material suitable for contact-free switching applications. Responsive conductive gels have gained attention owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, and related areas.
Keywords: Cyclodextrins; Supramolecular Hydrogels,

Isomer effect on energy storage of π-extended S-shaped double[6]heterohelicene - Kumar, Viksit; Bharathkumar, H. J.; Dongre, Sangram D.; Gonnade, Rajesh; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Angewandte chemie-international edition, 2023)
Recently, chiral and nonplanar cutouts of graphene have been the favorites due to their unique optical, electronic, and redox properties and high solubility compared with their planar counterparts. Despite the remarkable progress in helicenes, pi-extended heterohelicenes have not been widely explored. As an anode in a lithium-ion battery, the racemic mixture of pi-extended double heterohelical nanographene containing thienothiophene core exhibited a high lithium storage capability, attaining a specific capacity of 424 mAh g-1 at 0.1 A g-1 with excellent rate capability and superior long-term cycling performance over 6000 cycles with negligible fade. As a first report, the pi-extended helicene isomer (PP and MM), with the more interlayer distance that helps faster diffusion of ions, has exhibited a high capacity of 300 mAh g-1 at 2 A g-1 with long-term cycling performance over 1500 cycles compared to the less performing MP and PM isomer and racemic mixture (150 mAh g-1 at 2 A g-1). As supported by single-crystal X-ray analysis, a unique molecular design of nanographenes with a fixed (helical) molecular geometry, avoiding restacking of the layers, renders better performance as an anode in lithium-ion batteries. Interestingly, the recycled nanographene anode material displayed comparable performance. A pi-extended double heterohelical nanographene of thienothiophene core fused with two hexabenzocoronene units exhibits excellent performance as an anode in a lithium-ion battery. The isomer (PP and MM) with more interlayer distance exhibited a high lithium storage capability compared to the other isomer and racemic mixture. Helical nanographene anodes display excellent rate capability, superior long-term cycling performance, and recyclability.image
Keywords: Battery; graphene; Li-ion battery; nanographene; Organic Electrode Material

Polymerizable solvent-free organic liquids: a new approach for large area flexible and foldable luminescent films - Wakchaure, Vivek Chandrakant; Veer, Sairam Dnyaneshwar; Nidhankar, Aakash D.; Kumar, Viksit; Narayanan, Aswini; Babu, Sukumaran Santhosh (Angewandte chemie-international editon, 2023)
The high demand for light-emitting and display devices made luminescent organic materials as attractive candidates. Solvent-free organic liquids are one of the promising emitters among them due to the salient features. However, the inherent limitations of forming sticky and noncurable surfaces must be addressed to become an alternate emitter for large-area device applications. Herein, we functionalized solvent-free organic liquids having monomeric emission in bulk with polymerizable groups to improve the processability. The polymerizable group on carbazole, naphthalene monoimide, and diketopyrrolopyrrole-based solvent-free liquid emitters enabled on-surface polymerization. These emitters alone and in combinations can be directly coated on a glass substrate without the help of solvents. Subsequent photo or thermal polymerization leads to stable, non-sticky, flexible, foldable, and free-standing large-area films with reasonably high quantum yield. Our demonstration of the tunable and white light-emitting films using polymerizable solvent-free liquids might be a potential candidate in flexible/foldable/stretchable electronics. The new concept of polymerizable liquid can be extended to other functional features suitable for futuristic applications.
Keywords: Energy Transfer; polymerization; Solvent-Free Organic Liquids; Thin-Film; White Light

Thermally activated delayed fluorescent solvent-free organic liquid hybrids for tunable emission applications - Nidhankar, Aakash D. D.; Goudappagouda; Kothavade, Premkumar D.; Dongre, Sangram D.; Veer, Sairam Dnyaneshwar; Dash, Soumya Ranjan; Rajeev, Kavya; Unni, K. N. Narayanan; Shanmuganathan, Kadhiravan; Babu, Sukumaran Santhosh (Chemistry-An Asian Journal, 2023)
The synthetic feasibility and excellent luminescence features of organic molecules attracted much attention and were eventually found useful in lighting applications. In this context, a solvent-free organic liquid having attractive thermally activated delayed fluorescence features in bulk along with high processability has prime importance. Herein, we report a series of naphthalene monoimide-based solvent-free organic liquids exhibiting cyan to red thermally activated delayed fluorescence with luminescence quantum yields up to 80% and lifetimes between 10 to 45 mu s. An effective approach explored energy transfer between liquid donors with various emitters exhibiting tunable emission colors, including white. The high processability of liquid emitters improved the compatibility with polylactic acid and was used for developing multicolor emissive objects using 3D printing. Our demonstration of the thermally activated delayed fluorescence liquid will be much appreciated as a processable alternate emissive material suitable for large-area lighting, display, and related applications.
Keywords: 3D printing; Energy Transfer; OLED; Organic Liquids; TADF

Solvent-free organic liquids: an efficient fluid matrix for unexplored functional hybrid materials - Wakchaure, Vivek Chandrakant; Channareddy, Goudappagouda; Babu, Sukumaran Santhosh (Accounts of Chemical Research, 2024)
The invention of solvent-free organic liquids (SOLs) was serendipitous. However, the curiosity-driven research in the later stage delivered new soft materials with exciting optical, and optoelectronic properties along with appealing physical characteristics suitable for the futuristic applications. A slight change in the molecular design resulted in a drastic change in the physical state of molecules demonstrating monomer-like features in the bulk. The basic idea of core isolation has been successful in delivering new SOLs with attractive functional properties. The unique fluid matrix associated with SOLs offers a tremendous opportunity for making hybrid materials by simple mixing. The chance to study the fundamentally important electron transfer, energy transfer, charge transfer interactions, triplet-state emissions, and even detailed NMR experiments in the solvent-free neat state is the major attraction of SOLs. Usually, solvents and their polarity control such molecular properties, and in the case of SOLs, it avoids the use of solvents to study such fundamentally important properties. Besides, SOLs protect the triplet emitters and excited state processes involving triplet states from quenchers and make the analysis possible under ambient conditions. Our effort in this direction was focused on tuning the ground and excited state properties by transforming conventional organic molecules to SOLs and further value addition by preparing the hybrid SOLs. We developed a series of hybrid SOLs, exploring room-temperature phosphorescence, thermally activated delayed fluorescence, charge or energy transfer between donor and acceptor SOLs, selective explosive sensing, etc. A slight variation in the chemical structure or optoelectronic properties of the individual components imparted exciting optical features for the hybrid SOLs. It includes nonemissive charge transfer, tunable emission exciplex, room temperature phosphorescence, and thermally activated delayed fluorescence SOLs. The liquid matrix of donor SOLs accommodated varying amounts of acceptor SOLs to tune the ground and excited state features. In all examples of donor-acceptor-based hybrid SOLs, even a low amount of acceptor, such as a donor-acceptor ratio of 1000:1, can cause pronounced optical properties. Hence, the evaluation of the optical properties of SOLs, especially, in the absence of solvents is so special that it avoids the interference of solvent molecules. Still, the major drawback of SOLs remains unsolved until we report polymerizable SOLs. Although a large variety of SOLs have been reported in the literature, the long-lasting problem of surface stickiness of SOLs was resolved by polymerizable SOLs. It enabled the development of flexible, foldable, and stretchable large-area luminescent films suitable for lighting and display devices. In this Account, we summarize our work on SOLs, hybrid SOLs, polymerizable SOLs, and the application of SOLs in selective sensing of explosives. Finally, an outlook on the feasibility of luminescent polymerizable SOLs in futuristic applications is provided.

Tailoring helical ends of π-extended [6]heterohelicenes to control optical, and electrochemical features - Kumar, Viksit; Dongre, Sangram D.; Venugopal, Geethu; Narayanan, Aswini; Babu, Sukumaran Santhosh (Chemical Communications, 2024)
The inherent helical chirality and improved pi-stacking capabilities endow helicenes with fascinating photophysical characteristics when decorated with lateral pi-extensions. Here, we report the synthesis and physicochemical characterization of expanded hetero[6]helicenes fused with thiadiazole and selenadiazole rings at the helical ends. Comparing these heterohelicenes revealed the impact of the heteroatom-embedded aromatic rings on the excited state and redox features. A small structural variation of the terminal rings from thiadiazole to selenadiazole caused a striking change in the heterohelical nanographenes. The inherent helical chirality and improved pi-stacking capabilities endow helicenes with fascinating photophysical characteristics when decorated with heteroatoms.

Accessing electron-deficient π-extended pyrenes via non-K-region fusion - Dongre, Sangram D.; Kumar, Viksit; Kumar, Ravi; Babu, Sukumaran Santhosh (ORGANIC LETTERS, 2025)
This study presents a new class of pyrene derivatives featuring non-K-region fusion and electron-deficient pi-extension. By strategically introducing electron-withdrawing groups at the non-K positions, the optical and redox properties of these compounds were significantly altered. For the first time, we report a non-K-region fused acceptor pyrene with an extended pi-skeleton. The detailed characterizations revealed pronounced shifts in both absorption and emission spectra, accompanied by a significant lowering of the LUMO energy levels. Our results highlight non-K region-fused pyrenes as a promising building block for next-generation organic semiconductors with tunable electronic properties.

(Chiro)optical Properties of π-Extended Spiro-Double Carbo[7]helicene - Kumar, Viksit; Dongre, Sangram D.; Vandhanam, Aparna; Jadhav, Ashok Badrinarayan; Kumar, Jatish; Babu, Sukumaran Santhosh (Journal of Physical Chemistry Letters, 2025)
Helical nanographenes are a fascinating class of pi-extended chiral nanocarbons, where structural helicity imparts intrinsic chirality and unique optoelectronic properties to the rigid carbon framework. In this work, we synthesized a hexa-peri-hexabenzocoronene-based pi-extended spiro-double carbo[7]helicene. The helical distortion of the structure was unambiguously confirmed by X-ray crystallography. The optical properties were explored through UV-Vis absorption, fluorescence, and phosphorescence measurements, complemented by density functional theory (DFT) calculations. Remarkably, the pi-extended spiro-double carbo[7]helicene exhibited thermally activated delayed fluorescence (TADF) at room temperature and phosphorescence at low temperatures. Chiral HPLC successfully resolved the enantiomers into three fractions: (PP), (MM), and the meso forms (PM)/(MP), and chiroptical studies of the pure enantiomers revealed a moderately high g lum value of 1.58 x 10-3. Finally, the origin of the observed dissymmetry factors was rationalized by analyzing the transition electric dipole moments (TEDM) and transition magnetic dipole moments (TMDM) derived from time-dependent density functional theory (TD-DFT) calculations.

Chiroptical amplification of [7]-helicene nanographene by additional helical chirality - Dongre, Sangram D.; Venugopal, Geethu; Kumar, Viksit; Badrinarayan Jadhav, Ashok; Kumar, Jatish; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
Nanographenes have captivated scientific interest since the pioneering discovery of graphene. Recently, attention has shifted towards exploring chiral and nonplanar nanographenes, for their distinct optical, chiroptical, and electronic properties. Despite the growing acceptance of helicenes, the research on inducing helical chirality on pi-extended derivatives to boost chiroptical properties remains unattended. In our study, we introduce a new pi-extended [7]-helicene resulting from the condensation of diamines with 3,6-dibromophenanthrene-9,10-dione, complemented by two hexabenzocoronene arms in the periphery. Notably, the nanographene containing binaphtho-[1,4]diazocine, compared to the corresponding phenazine, exhibits a remarkable average 2.5, 5, and 10-fold enhancements in quantum yield, dissymmetry factor, and brightness, respectively, when measured in five different solvents. These improvements underscore the significance of the induced helical chirality by the antiaromatic binaphtho-[1,4]diazocine in influencing the chiroptical properties of the helical nanographene. Our research represents a significant stride toward unlocking the potential of pi-extended helicenes and lays the groundwork for further exploration in designing and synthesizing new chiral nanomaterials.
Keywords: circularly polarised luminescence; dissymmetry factor; helicene; nanographene; quantum yield

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene

Multifunctional luminogens with synergy of aggregation-induced delayed fluorescence, two-photon absorption and photocurrent generation - Chatterjee, Abhijit; Narayanan, Sundaravalli; Thorat, Sachin; Malik, Ajay J.; Ambhore, Madan D.; Narayanan, Aswini; Sihag, Anil Kumar; Babu, Sukumaran Santhosh; Lahiri, Mayurika; Hazra, Partha (Chemical Communications, 2025)
In this study, we investigated the aggregation-induced delayed fluorescence (AIDF) properties of three luminogens - TN, TA, and TP. Our comprehensive theoretical analysis reveals a significant reduction in the Delta EST in their aggregated or solid-state, activating TADF, on a similar to mu s time-scale. Additionally, these luminogens demonstrate two-photon excited anti-Stokes photoluminescence emission and improved photocurrent generation, attributed to their strong charge transfer characteristics and longer singlet exciton lifetimes.

Regioisomeric π-extended nanographene with long-lived phosphorescence afterglow - Kumar, Viksit; Venugopal, Geethu; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Gonnade, Rajesh; Kumar, Jatish; Ruer, Paul C.; Hupp, Benjamin; Steffen, Andreas; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2025)
The cutouts of graphene sheets, particularly those with a nonplanar topology, present vast opportunities for advancement. Even a slight deviation from the planar structure can lead to intriguing (chiro)optical features for helically twisted nanographenes. In this context, we introduce two regioisomeric pi-extended nanographenes that exhibit distinct excited-state characteristics. The helicene structure and the photophysical features can be easily tuned by changing the connecting position of the nanographene to the carbazole core (2,7- and 3,6-). Single-crystal X-ray diffraction analysis confirmed the formation of nanographenes with bent and helical conformations. Both derivatives exhibited thermally activated delayed fluorescence at room temperature and phosphorescence at low temperatures. Notably, the nanographene with the bent structure displayed an impressive red afterglow lasting over 30seconds, in contrast to the very weak afterglow observed in the helical structure. DFT calculations revealed the existence of an isoenergetic higher triplet state (T-8) and comparatively weak spin-orbit coupling (T-1-S-0), thereby enabling the bent nanographene to exhibit a long-lived component and strong afterglow. Our findings highlight the significance of regioisomeric nanographenes with exceptional optical properties and offer a deeper understanding of the structure-property relationship in nonplanar nanographenes.
Keywords: Afterglow; CPL; Helicenes; nanographene; Phosphorescence; TADF

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide